Hydraulic analysis of existing semi-separate sewage system by using SWMM - Goce TASESKI, Petko Pelivanoski (Ss Cyril and Methodius University, Civil Engineering Faculty – Skopje, 2019)
Sewage systems in the Republic of North Macedonia are designed and constructed as separate sewage systems for sanitary and storm water, but in practice, in the majority of cases they function as semi-separate or combined systems. This owes to the fact that a small number of the inhabited places have a completely built system, i.e. in parts of the urban area there is no sanitary or storm water sewage system. In such case, users of the system, regardless of the network type and the wastewater type, use the existing sewage system by which mixing of water in the collectors occurs. The aim of this paper is, through the hydraulic analysis of an existing semi-separate sewage system, by means of the software package SWMM, to determine the influence of storm water on the maximum capacities - permeability of the collectors. Also, it is well known that storm water carries solid particles such as sand, soil, gravel which subsequently deposit in the collectors since they have not been anticipated in the phase of designing and construction to receive deposit particles. Therefore, the model will present the influence of pipe fullness with deposits on collector capacity.
Keywords: Sewer system, Storm system, hydraulic model, SWMM